Laminated jute and glass fibre reinforced composite for repairing concrete through wrapping technique - Yaakob, Mohd Yuhazri; Husin, Mohd Amirhafizan; Hel Mee, Umarfaruq; Lau, Saijod Tze Way; Amir Mohamed, Kamarul; Zulfikar, Achmad Jusuf (UTHM Publisher, 2023)
Natural fiber reinforced composite in concrete structure material has attracted many researchers and engineers in recent decades due to its good agreement in mechanical properties, economics, and sustainability. An experimental investigation was conducted to investigate the jute and glass fiber laminated composite for cylindrical concrete repair. Jute and glass fiber were used as reinforcement, and vinyl ester (VE) served as the matrix. The vacuum bagging technique was used to wrap the cylindrical concrete columns with a diameter of 50 mm and a height of 150 mm. Compression and Brazilian tests were performed on the specimen. It was discovered that the four (4) layers of jute fiber reinforced thermoset (JFRT) composite had the highest mechanical properties, with an improvement of 72.62%when compared to glass fibre reinforced thermoset (GFRT) composite. It can be concluded that both GFRT and JFRT had the potential to improve the mechanical properties performance of cylindrical concrete specimens with an increase of up to five (5) layers of woven fiber. The results presented here may facilitate improvements in the concrete specimen by using JFRT where it was suggested to have a higher improvement for the concrete specimen with the optimum layers applied. As a result, jute fiber has been shown to perform better and can be used as an alternative to glass fiber. As a result, jute fiber has been shown to perform better and can be used as an alternative to glass fiber.